An Analysis of the Relationship between the Boycott of Israeli-Affiliated Products and Indonesia’s Noble Values - Ferreri, Vincensius Sebastian (De Cive : Jurnal Penelitian Pendidikan Pancasila dan Kewarganegaraan, 2025)
The escalation of the Israel-Palestine conflict on October 7, 2023, triggered various global responses, including a boycott movement against products affiliated with Israel. This study aims to examine the relationship between boycott actions and Indonesia’s noble values, such as the second principle of Pancasila and the Preamble to the 1945 Constitution. A descriptive qualitative approach was employed, with interviews conducted with 13 Universitas Brawijaya students selected through purposive sampling until data saturation was reached, supported by literature studies. Data were analyzed through the stages of simplification, presentation, and conclusion drawing. The results show that the boycott action is not only a form of global solidarity but also reflects the implementation of humanity and justice values that form the foundation of Indonesia’s philosophy. This study affirms that boycotts can serve as a collective movement to support world peace, in line with Pancasila principles and the spirit of Indonesian nationalism. The findings also indicate that students' awareness of global issues plays an important role in strengthening national character.